Does low synchronicity mean more or less informative prices? Evidence from an emerging market - Li, Mingsheng; Liu, Desheng; Peng, Hongfeng; Zhang, Luxiu (Journal of Financial Stability, 2020)
We investigate a controversial and hotly debated issue of whether low stock return synchronicity (SRS) means more or less informative stock prices using three exogenous events: an anti-corruption campaign launched by the Chinese Government, a stock market crash in China, and firms’ public exposure of fraud. Investigating the changes in SRS associated with these events helps mitigate endogenous issues since these events have distinctive relationships with companies’ stock price informativeness. Our results show that firms’ SRS declines significantly after the anti-corruption campaign aiming to improve corporate governance and after firms’ public exposure of fraud. The SRS is substantially higher during and after the stock market crises. Firms located in more developed regions have lower SRS than those in less developed regions. These results consistently indicate an inverse relationship between the SRS and stock price informativeness.